On the concept of ‘music performance’ in the context of the COVID-19 lockdown: A brief musicological discussion based on a public survey among listeners in Argentina - Magdalena Zorn; Juan Manuel García (INSAM)
In this work, the concept of music performance in the context of the Covid-19 lockdown is assessed through a brief musicological discussion based on a public survey performed on the broad population in Argentina during the lockdown. Traditionally, listeners and performers interact in concert halls sharing the same space and time. During the Covid-19 lockdown, listeners and performers were obliged to stay home and thus, online music consumption in the genres of Classic, Jazz, Pop and Folk became “state of the art”. With the increasing importance of performances through the internet, the interaction between listeners and performers substantially changed. Given that the context of a live performance on the internet is so different to that of one in a concert hall, we conducted a public anonymous survey during the lockdown in July and August 2020 to question listeners in the broad population of Argentina about both paradigms. With regards to the studied sample, listeners and performers seem to agree that live emissions via the internet do not suit their preferences of interaction as well as a music performance in a concert hall.